2022
DOI: 10.31436/ijcs.v5i2.252
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness and Practice on Dietary Management Among Patients with Urolithiasis: A Scoping Review

Abstract: Urolithiasis or kidney stone has strong association with lifestyle. The pattern of recurrent episodes reported is alarming and if left untreated will lead to serious conditions such as cancer or ablative surgical intervention. Therefore, this scoping review was performed to provide an overview on knowledge, awareness and practice (KAP) of dietary management among patients with urolithiasis. Published studies within 2010 until 2020 on KAP among urolithiasis patients globally and Malaysia were searched through f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…There are studies that suggested a prevalence of 10-15% globally and up to 20% among Saudis. On the other hand, our study showed a 10% prevalence among the Alahsa population [8][9][10]. Our study found a higher incidence among those aged 35 to 50, which is consistent with many other studies [8,10,11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There are studies that suggested a prevalence of 10-15% globally and up to 20% among Saudis. On the other hand, our study showed a 10% prevalence among the Alahsa population [8][9][10]. Our study found a higher incidence among those aged 35 to 50, which is consistent with many other studies [8,10,11].…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted in Malaysia showed that there are low levels of awareness about risk factors and symptoms of renal stones, and there is a lack of sufficient knowledge about the role of diet in the medical management of renal stones [ 8 ]. Another study conducted in Saudi Arabia showed the level of awareness about risk factors and prevention among communities.…”
Section: Introductionmentioning
confidence: 99%
“…( 1234567890 The present work identified strong differences in the KAP scores of individuals with different demographic characteristics, including age, gender, BMI, residence, education and other socioeconomic and medical characteristics. A strong association between this disease and socioeconomic status, particularly income, has been previously established 20 , which also reflected on the KAP levels of the patients 21 . Our analysis of respondents revealed a notable deficiency in knowledge concerning urinary stones, particularly in areas related to preventive dietary recommendations and lifestyle habits, such as reducing the consumption of animal protein-rich foods and foods high in citric acid.…”
Section: Discussionmentioning
confidence: 80%
“…Cutting back on foods rich in citric acid like oranges, pineapples, and grapes can help in preventing urinary system stones". In this context, there has been limited exploration of the KAP regarding healthy habits and urinary stones among both patients and the general public, both globally and specifically within China 21 . An investigation conducted in Atlanta, United States of America, revealed that local individuals with urinary stones lacked a proper understanding of how to manage their diet and the related risk factors 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation